Collection of Plasma Samples in Areas with Limited Healthcare Access - Johnson, Alicia; Braga, Camila; de Magalhães Padilha, Pedro [UNESP]; Adamec, Jiri (Springer Nature, 2023)
Regular monitoring of various biomarkers and molecular panels in plasma can significantly help to prevent disease onset and improve its management and final outcomes. Many groups can benefit from monitoring programs focusing on the prevention of cardiovascular diseases, evaluation of environmental exposure impacts, or the prevention/management of cancer. Improvement in therapeutic options in part due to targeted therapeutic agents and monoclonal antibody therapies has led to a significant sized population that can be described as cancer survivors. These patients, although in remission from their original disease, are at significant risk for the recurring disease and must be monitored for adverse events. Monitoring is, however, not an easy task; requiring a high level of complexity in lab facilities and blood/plasma sampling, collection, and storage must occur under tightly controlled conditions. These demanding circumstances are especially difficult to attain in rural areas and in historically marginalized populations. The Telimmune Plasma Separation Card (TPS card or TPSC) has been developed to enable diagnostic plasma sampling, collection, and stabilization in locations that may be remote to laboratory or clinic. The TPSC requires a drop of blood applied to a top of a separation system consisting of a separation membrane and collection disk. In 3 min, the TPSC device separates plasma from erythrocytes and deposits a defined volume of plasma into a collection disc which is air-dried for 15 min to deliver a stabilized, volumetric plasma sample, which may be stored or shipped at ambient temperatures with minimal biological risk. Extraction of proteins and metabolites is then achieved in well-equipped laboratories using protocols discussed in this chapter.
Keywords: Biomarkers; Metabolomics; Micro-sampling; Plasma collection; Proteomics; Tissue